Migration through the Darién Gap: Between Social Invisibility and Exclusion - Alonso Sandoval, Tomás Cristóbal (2024)
This research aims to analyze the humanitarian crisis in the Darién Gap, focusing on the social invisibility and exclusion faced by thousands of migrants traversing this jungle on their way to the United States. The study employed documentary analysis and selected key texts related to Human Rights and International Law pertinent to the subject matter. The methodology used is dogmatic and comparative, with the purpose of critiquing the migratory phenomenon. Among the main findings, various solutions are proposed from a legal perspective to address the current issues.